The effect of Robinson's strategy on the achievement of art education students in art history (Journal of the College of Basic Education, 2022)
The study aimed at the effect of Robinson's strategy on the achievement of art education students in the subject of artistic taste.. To achieve the goal of the research, the researchers used the experimental design with two equal groups, experimental and control, with a pre and post test for the subject of artistic taste., to suit it on a sample of students of the Department of Art Education / College of Basic Education / the first stage. In order to reach the results of the research, the research tool was represented by a cognitive achievement test for the subject of artistic taste., the researchers analyzed the data into systematic images for their research using the statistical package for social sciences (spss).The most important results of the search showed the following:The interaction process provided by this strategy increased the students' ability to memorize information and understand it correctly, in a scientific and practical way.The use of Robinson’s strategy gives students the ability to generate questions through the survey process and an introductory view of the topic and the possibility of raising them in the lesson. It also generates ideas, excitement and curiosity for the purpose of the scientific study of each topic in the lesson.Recommendations: In light of the results and conclusions reached by the researchers, they recommend a number of recommendations, including:1- The necessity of using Robinson's strategy in other subjects for other stages, and investigating its impact on student achievement.2- Providing the necessary equipment and devices and preparing books, resources and modern teaching aids in educational and educational institutions to facilitate the use of Robinson's strategy.Suggestions:To complement and develop the current research, the researcher suggested the following:Conducting a similar experimental study using Robinson's strategy in the subject of artistic taste.